Model and method of assessment risks protection of personal data during their processing at the automated system - Корченко, Олександр Григорович; Дрейс, Юрій Олександрович; Лозова, Ірина Леонідівна (Ukrainian Information Security Research Journal, 2016)
The question of the need to protect personal data created and processed by application software in automated systems. Analysis of the existing legislation indicates mandatory protection of state information resources or classified information, protection of which is defined by law. Since personal data can be attributed to confidential information about a person, they need protection at the application of the integrated system of information security. Its implementation involves a risk assessment of threats during the development of security policy in the definition of necessary measures and information security. A basic model presenting risk parameters defined criteria in the legislation in the field of personal data protection. The method of risk assessment which resulted in recommendations for selecting the policy of personal data protection, addition of standard functional profile protection security services as required, determination of the damage caused to a person, society and state in case of loss this personal data.